A high-throughput method for determining the amylose content of rice - Fei Chen; Yunsheng Song; Minghui Dong; Yulin Xie; Zhongying Qiao; Yongliang Zhu; Penghui Cao; Yajie Yu; Caiyong Yuan (PLoS ONE, 2025)
Rice is one of the world’s most abundant food crops. The amylose content is a key factor affecting the production of high-quality rice. The commonly used method for determining the amylose content is the Iodine-Starch colorimetric method. Due to the limitations of traditional iodine colorimetric methods, this experiment provides a simple high-throughput method (SSDM) for determining amylose content. Using rice varieties with different genetic backgrounds as experimental materials, the accuracy and practicality of the new method were explored to improve measurement efficiency and simplify the operation process. The results demonstrated a strong correlation (R = 0.9998) between the absorbance values and amylose content, with a relative deviation of less than 1.2%. It showed good repeatability, with a variation range of 0.43% to 1.63%. The experiment takes a short time and can measure 96 samples at once. Therefore, while ensuring the accuracy of experimental results, the high-throughput measurement method improves the efficiency of measuring amylose content. This has important practical significance for early screening and identification of excellent individuals in rice quality genetic breeding programs.